Cerebral Autoregulation and Brain Networks in Occlusive Processes of the Internal Carotid Artery. Issue 2 (February 2015) - Avirame, Keren; Lesemann, Anne; List, Jonathan; Witte, Anja Veronica; Schreiber, Stephan Joachim; Flöel, Agnes
Patients with unilateral occlusive processes of the internal carotid artery (ICA) show subtle cognitive deficits. Decline in cerebral autoregulation and in functional and structural integrity of brain networks have previously been reported in the affected hemisphere (AH). However, the association between cerebral autoregulation, brain networks, and cognition remains to be elucidated. Fourteen neurologically asymptomatic patients (65±11 years) with either ICA occlusion or high-grade ICA stenosis and 11 age-matched healthy controls (HC) (67±6 years) received neuropsychologic testing, transcranial Doppler sonography to assess cerebral autoregulation using vasomotor reactivity (VMR), and magnetic resonance imaging to probe white matter microstructure and resting-state functional connectivity (RSFC). Patients performed worse on memory and executive tasks when compared with controls. Vasomotor reactivity, white matter microstructure, and RSFC were lower in the AH of the patients when compared with the unaffected hemisphere and with controls. Lower VMR of the AH was associated with several ipsilateral clusters of lower white matter microstructure and lower bilateral RSFC in patients. No correlations were found between VMR and cognitive scores. In sum, impaired cerebral autoregulation was associated with reduced structural and functional connectivity in cerebral networks, indicating possible mechanisms by which severe unilateral occlusive processes of the ICA lead to cognitive decline.